STRUCTURAL CHANGES IN RUSSIA’S INDUSTRY: THE CURRENT SITUATION AND FORECAST - Belkin, Yuri; Ryzhakova, Alla; Sedova, Nadezhda; Shishkin, Anatoly (Journal of Applied Engineering Science, 2021)
Purpose: The objective of this paper is to analyze the dynamics of change in industrial production in Russia from 2008 to 2019 across a set of indicators characterizing structural changes in industry, specifically its extractive, manufacturing, and production and distribution of electricity, gas, and water sectors. Design/Methodology/Approach: The work provides a forecast of output in the three sectors of industry using methods such as Holt’s method and factor analysis, with structural shifts projected using the methods of Szalai, Ryabtsev, Gatev, and Kazinets.Findings: The empirical results show further changes in the structure of industrial production in the Russian Federation and an increase in manufacturing production at the same time due to a decrease in production by the type of activity "Mining".Practical Implications: Investors who plan to invest in the Russian Federation should bear in mind that investments in manufacturing production are advisable.Originality/value: To initiate progressive structural changes, the development and qualitative transformation of the structure of the manufacturing industry is necessary
Keywords: industry; structural changes; forecasting; COVID-19